Conformity and Changes in the Radiological Neck and Shoulder Balance Parameters Throughout 3-Year Follow-up Period: Do They Remain the Same?. Issue 6 (15th March 2020) - Chiu, Chee Kidd; Chan, Chris Yin Wei; Tan, Pheng Hian; Goh, Saw Huan; Ng, Sherwin Johan; Chian, Xue Han; Ng, Yun Hui; Ler, Xin Yi; Chandren, Josephine Rebecca; Chung, Weng Hong; Kwan, Mun Keong
Abstract : Study Design: Retrospective study. Objective: The primary objective of this study was to assess the conformity of the radiological neck and shoulder balance parameters throughout a follow-up period of more than 2 years. Summary of Background Data: Postoperative shoulder and neck imbalance are undesirable features among Adolescent Idiopathic Scoliosis patients who underwent Posterior Spinal Fusion. There are many clinical and radiological parameters used to assess this clinical outcome. However, we do not know whether these radiological parameters conform throughout the entire follow-up period. Methods: This was a retrospective study done in a single academic institution. Inclusion criteria were patients with scoliosis who underwent posterior instrumented spinal fusion with pedicle screw fixation and attended all scheduled follow-ups for at least 24 months postoperatively. Radiological shoulder parameters were measured from both preoperative antero-posterior and postoperative antero-posterior radiographs. Lateral shoulder parameters were: Radiographic Shoulder Height, Clavicle Angle (Cla-A), Clavicle-Rib Intersection Difference, and Coracoid Height Difference. Medial shoulder and neck parameters were: T1 Tilt and Cervical Axis (CA) . Results: The radiographs of 50 patients who had surgery done from November 2013 to November 2015 were analyzed. Mean age of this cohort was 16.3 ± 7.0 years. There were 38 (76%) female patients and 12 (24%) male patients. Mean final follow-up was 38.6 ± 5.8 months. When conformity assessment of the radiological parameter using the interclass coefficient correlation was done, we found that all parameters had significant correlation ( P < 0.05). T1 tilt (0.78) had good reliability, CA (0.47), Clavicle-Rib Intersection Difference (0.43), and Coracoid Height Difference (0.40) had moderate reliability and Radiographic Shoulder Height (0.22) and Cla-A (0.13) had poor reliability. Conclusion: All the radiological shoulder and neck balance parameters studied were conformed and suitable to be used to assess the patient postoperatively. Amongst these radiological parameters, T1 tilt followed by CA recorded to be the most reliable parameters over time. Level of Evidence: 4 Abstract : This study assessed the conformity of radiological neck and shoulder balance parameters throughout a follow-up period of more than 2 years and found they were conformed and suitable to be used to assess the patient postoperatively. Amongst these parameters, T1 tilt followed by CA recorded to be the most reliable.